Advokasi Dakwah Dalam Budaya Lokal "Balimau" Menyambut Bulan Ramadhan Di Padang Sumatera Barat - M. Ridwan; Bukhari Bukhari (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2010)
"Balimau" as a cultural heritage of the past is associated with fasting Ramadan. "Balimau" welcomes the month of Ramadan is a tradition for the people of Padang, West Sumatra. "Balimau" / toiletries contain a unique coming value. "Balimau", itself is a shower using water mixed with lime or orange. Aside from being an overflow of excitement, self-cleaning also comes. The purpose of "Balimau" is to purify oneself before entering the month of Ramadan, this form of self-purification by bathing in rivers and lakes, washing with oranges and fragrant potpourri. After "Balimau" then forgive because it will enter the month of Ramadan, evening prayer tarawih and the next day fasting. In addition there is also "Balimau" which is done in the bathroom by applying spices and fragrances to a container filled with water and then shampooing the fragrance. However, the "Balimau" tradition has shifted values from positive to come, not even in accordance with the teachings of the Islamic religion, for example, purifying oneself was polluted with the practice of bathing together without the veil between men and women in public baths. Therefore the Majlis Ulama of West Sumatra issued a fatwa that "Balimau" welcoming the holy month of Ramadan is forbidden in Islam